Advanced operating systems and kernel applications [ techniques and technologies - Jiang, Song; Wiseman, Yair , 1970- (Gale virtual reference library, 2010)
"This book discusses non-distributed operating systems that benefit researchers, academicians, and practitioners"--Provided by publisher